Creation and the cross : the mercy of God for a planet in peril - Johnson, Elizabeth A., 1941-- (Maryknoll, New York : Orbis Books, 2018)
In this fresh creative approach to theology, Elizabeth Johnson asks how we can understand cosmic redemption in a time of advancing ecological devastation. In effect, how can we extend the core Christian belief in salvation to include all created beings? Immediately this question runs into a formidable obstacle: the idea that Jesus's death on the cross was required as atonement for human sin-- a theology laid out by the eleventh-century theologian St. Anselm. Constructing her argument (like Anselm) in the form of a dialogue, Johnson lays out the foundations in scripture, the teachings of Jesus, and the early Church for an understanding that emphasizes the love and mercy of God, showing how this approach can help us respond to a planet in peril.
Conversion of heart and mind : us.
Includes bibliographical references.
Keywords: Anslem, Saint, Archbishop Canterbury, 1033-1109; Redemption -- Christianity; Ecotheology; Restoration ecology; Atonement; God (Christianity) -- Love; Creation